The Legal Impacts And The Government’S Efforts To Respond To Electronic State Administrative Decisions Following The Enactment Of Law No. 11 Of 2020 On Job Creation - Marojahan JS Panjaitan (Prophetic Law Review, 2022)
Responses to applications for state administrative decisions within a time frame of 10 working days as regulated in Article 53 of the Law No. 30 of 2014, which apparently does not provide legal certainty to applicants. This condition is attributed to the fact that electronic form of applications within the 10 working days will not automatically be granted, unless applicants apply to the State Administrative Court. On that basis, the provisions of Article 53 of the Law No. 30 of 2014 were amended by Law No. 11 of 2020 to guarantee the applicants that their electronic form of application within the time limit of five working days will be granted without going through a judicial process. Thus, this study aims to address two aspects, the legal impacts of the issuance of Electronic State Administrative Decree after the enactment of Law No. 11 of 2020, and the government’s efforts to respond to the issuance of Electronic State Administrative Decree after the enactment of Law No. 11 of 2020. The research was conducted using normative legal research, particularly library sources, and secondary data in the form of primary, secondary, and tertiary legal materials. The study showed that the legal impacts of an electronically submitted application for a state administrative decision according to Article 53 of the Law No.11 of 2020 have the same legal force as a state administrative decision issued directly by a government official. Clearly, the government’s efforts to issue electronic form of application for the State Administrative Decisions by individuals and/or legal entities after the enactment of Law No. 11 of 2020 are carried out to build digital-based governance in all lines of government.Keywords: government actions, decrees, permits. Dampak Hukum Dan Upaya Pemerintah Merespon Keputusan TUN Secara Elektronik Pasca Berlakunya Undang-Undang Nomor 11 Tahun 2020 Tentang Penciptaan Lapangan Kerja Abstrak Tanggapan atas permohonan keputusan tata usaha negara dalam jangka waktu 10 hari kerja sebagaimana diatur dalam Pasal 53 Undang-Undang Nomor 30 Tahun 2014, yang ternyata tidak memberikan kepastian hukum kepada pemohon. Kondisi ini disebabkan karena permohonan formulir elektronik dalam waktu 10 hari kerja tidak otomatis dikabulkan, kecuali pemohon mengajukan permohonan ke Pengadilan Tata Usaha Negara. Atas dasar itu, ketentuan Pasal 53 Undang-Undang Nomor 30 Tahun 2014 diubah dengan Undang-Undang Nomor 11 Tahun 2020 untuk menjamin pemohon bahwa formulir permohonan elektronik mereka dalam batas waktu lima hari kerja akan diberikan tanpa melalui sebuah proses peradilan. Dengan demikian, penelitian ini bertujuan untuk membahas dua aspek, yaitu dampak hukum dari diterbitkannya TUN secara Elektronik pasca berlakunya Undang-Undang Nomor 11 Tahun 2020, dan upaya pemerintah dalam merespon terbitnya TUN secara Elektronik pasca berlakunya Undang-Undang Nomor 11 Tahun 2020. Undang-Undang Nomor 11 Tahun 2020. Penelitian dilakukan dengan menggunakan penelitian hukum normatif, khususnya sumber kepustakaan, dan data sekunder berupa bahan hukum primer, sekunder, dan tersier. Hasil penelitian menunjukkan bahwa dampak hukum dari Permohonan TUN yang diajukan secara elektronik menurut Pasal 53 Undang-Undang Nomor 11 Tahun 2020 memiliki kekuatan hukum yang sama dengan keputusan TUN yang dikeluarkan langsung oleh pejabat pemerintah. Jelasnya, upaya pemerintah untuk menerbitkan Surat Keputusan Tata Usaha Negara secara elektronik oleh orang perseorangan dan/atau badan hukum pasca berlakunya Undang-Undang Nomor 11 Tahun 2020 dilakukan untuk membangun pemerintahan berbasis digital di semua lini pemerintahan.Kata kunci: tindakan pemerintah, keputusan, izin.